2022
DOI: 10.3390/su14148725
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Efficacy and Learning Conformity among Chinese University Students: Differences by Gender

Abstract: Background: Although past research highlights the impact of self-efficacy on university students’ learning motivation, examining potential links with specific types of learning conformity is limited. The current study examined associations between Chinese university students’ perceived self-efficacy and learning conformity across different types of learning motivation.Methods: A total of 339 Chinese university students were surveyed using the General Self-Efficacy Scale and the Learning Conformity Scale. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Gender inequality does not appear to be supported by current findings in the school setting. Female students have lower self-efficacy than male students in the learning process and are more likely to be academically compliant ( Xiao & Song, 2022 ). These conflicts remain to be verified by transferring to a larger heterogeneous sample.…”
Section: Discussionmentioning
confidence: 99%
“…Gender inequality does not appear to be supported by current findings in the school setting. Female students have lower self-efficacy than male students in the learning process and are more likely to be academically compliant ( Xiao & Song, 2022 ). These conflicts remain to be verified by transferring to a larger heterogeneous sample.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in South Korea found persistent gender differences in adolescents' levels of self-control, with males having lower self-control than females [45]. Secondly, an experiment conducted in 2022 with Chinese undergraduate students showed gender differences in self-efficacy, showing that the overall self-efficacy of female college students is lower than that of male college students [46]. Finally, studies by Cla and Sallis validated gender differences in PA [47,48].…”
Section: Self-control As a Mediating Mechanismmentioning
confidence: 95%
“…Previous studies on general self-efficacy mainly used cross-sectional data [ [8] , [9] , [10] ], a few longitudinal studies had insufficient sample sizes [ 11 ], and most participants were from the same university [ 12 ]. Furthermore, studies noticed the average trajectory of general self-efficacy but ignored the heterogeneity among different groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%